2021
DOI: 10.1186/s12885-021-08864-8
|View full text |Cite
|
Sign up to set email alerts
|

“Chronic fatigue, quality of life and long-term side-effects of chemotherapy in patients treated for non-epithelial ovarian cancer: national case-control protocol study of the GINECO-Vivrovaire rare tumors INCa French network for rare malignant ovarian tumors”

Abstract: Background Germ cell tumors and sex cord stromal tumors are rare cancers of the ovary. They mainly affect young women and are associated with a high survival rate. The standard treatment mainly involves conservative surgery combined with chemotherapy [bleomycin, etoposide and cisplatin (BEP)] depending on the stage and the prognostic factors, as for testicular cancers. As reported in testicular cancer survivors, chemotherapy may induce sequelae impacting quality of life, which has not yet been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Our results also demonstrated that advanced-stage OC survivors had experienced higher levels of fatigue similar to the previous findings on this subject [ 42 ]. Muscle strength, neuropathy, mobility, depression, anxiety, and exercise intolerance may all contribute to fatigue [ 7 , 33 ], which may explain the difference between OC survivor subgroups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results also demonstrated that advanced-stage OC survivors had experienced higher levels of fatigue similar to the previous findings on this subject [ 42 ]. Muscle strength, neuropathy, mobility, depression, anxiety, and exercise intolerance may all contribute to fatigue [ 7 , 33 ], which may explain the difference between OC survivor subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…OC patients commonly experience a varied range of physical and psychological symptoms resulting from the chronic disease process and the adverse effects of these treatments [ 2 , 6 ]. These symptoms and related consequences include neuropathy, loss of muscle strength, fatigue, decreased mobility, exercise intolerance, dyspnea, and diminished health-related quality of life [ 7 , 8 ]. Furthermore, the adverse effects of local and systemic treatments on health-related components of physical fitness (muscle strength, exercise capacity, body composition) may still persist even during the survival phase of OC [ 8 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…These suggested that surgery and chemotherapy should be operated in ovarian cancer patients based on the feasibility conditions of patients to improve the outcome of these patients. In addition, chemotherapy might be associated with some side-effects such as fatigue in patients, and intervention strategies should be proposed to improve the management of these patients during their treatment and in the long term ( 41 ). In the past, ovarian cancer was found to be a radiosensitive tumor, and radiation was one of the main therapies for patients with epithelial ovarian cancer, which was applied to manage patients with low residual volumes of disease ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…GOG-NTX uses 11 items to describe peripheral nerve disorders, such as numbness, discomfort, arthralgia, deep sensitivity problems and walking disorders. The detailed description has also been discussed in a previous study 27. A combination of these questionnaires can help demonstrate the life status of MOGCT patients after treatment.…”
Section: Methods and Analysismentioning
confidence: 99%